SEM Evaluation of the Marginal Gap of Zirconia-Reinforced Lithium Silicate Full Crowns and the Effect of Post Crystallization: An In Vitro Study - Asaf Shely; Diva Lugassy; Maxim Anufriev; Joseph Nissan; Olisya Rauchwerger; Gil Ben-Izhack (MDPI AG, 2024)
Background: This study compared the influence of crystallization on marginal gap adaptation by using computer-aided design and manufacturing (CAD-CAM) for producing monolithic zirconia-reinforced lithium silicate (ZLS) ceramic crowns. Methods: A total of 25 plastic teeth were scanned using a Primescan intra-oral scanner (IOS), and ZLS crowns were ground. For each unit (abutment and crown), the marginal gap was evaluated pre crystallization and post crystallization at four regions of interest through the use of a scanning electron microscope (SEM). To compare the marginal gap between the two groups, a Kolmogorov-Smirnov test performed on the study variables indicated a normal distribution (p > 0.05) followed by paired samples T-tests (α = 0.0005). Results: After crystallization, there were significantly higher circumferential marginal gaps (CMGs) for all four surfaces (distal (p = 0.0005), mesial (p = 0.0005), palatal (p = 0.0005), and buccal (p = 0.0005)). The total mean marginal gap (MMG) revealed a significantly higher result for the post-crystallization group (79.82 ± 7.86 μm) compared to the pre-crystallization group (24.25 ± 5.49 μm). Conclusions: The post-crystallization group showed a significantly higher marginal gap compared to the pre-crystallization group in all parameters, but both groups were in the clinically accepted threshold (<120 microns). In terms of the marginal gap, it is arguable whether to carry out post-crystallization for CELTRA® DUO crowns and achieve better mechanical properties but significantly increase the marginal gap.